1996
DOI: 10.1142/s0218195996000022
|View full text |Cite
|
Sign up to set email alerts
|

Output Sensitive Construction of the Delaunay Triangulation of Points Lying in Two Planes

Abstract: In this paper, we propose an algorithm to compute the Delaunay triangulation of a set [Formula: see text] of n points in 3-dimensional space when the points lie in 2 planes. The algorithm is output-sensitive and optimal with respect to the input and the output sizes. Its time complexity is O(n log n+t), where t is the size of the output, and the extra storage is O(n).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
1

Year Published

2000
2000
2013
2013

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 11 publications
0
10
0
1
Order By: Relevance
“…1 He gives two examples: the computation of 3D Delaunay complexes of sets lying in two planes [8], and optimal Möbius transformation and conformal mesh generation [5]. Hyperbolic geometry is also used in applications like graph drawing [29,24].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…1 He gives two examples: the computation of 3D Delaunay complexes of sets lying in two planes [8], and optimal Möbius transformation and conformal mesh generation [5]. Hyperbolic geometry is also used in applications like graph drawing [29,24].…”
Section: Introductionmentioning
confidence: 99%
“…Several years ago, we showed that the hyperbolic Delaunay complex and Voronoi diagram can easily be deduced from their Euclidean counterparts [18,8]. As far as we know, this was the first time when the computation of hyperbolic Delaunay complexes and Voronoi diagrams was addressed.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Esta representación de las esferas constrasta con otras representaciones utilizadas recientemente por otros autores como [Ped88], [DMT92], [BC+91], [BC+92] y [D&G94], que han representado una esfera como un punto en  4 (o un círculo como un punto en  3 ) mediante la 4-tupla (x,y,z,R) donde el radio de la esfera es r=x 2 +y 2 +z 2 -R. Si bien este tipo de representación tiene sus ventajas en la geometría computacional, no es así para el modelado que se presenta en este capítulo.…”
Section: Espacio Vectorial Esféricounclassified